2021
DOI: 10.1021/acs.nanolett.1c03435
|View full text |Cite
|
Sign up to set email alerts
|

Organic-2D Material Heterostructures: A Promising Platform for Exciton Condensation and Multiplication

Abstract: We predict that high temperature Bose−Einstein condensation of charge transfer excitons can be achieved in organic-two-dimensional (2D) material heterostructures, at ∼50− 100 K. Unlike 2D bilayers that can be angle-misaligned, organic-2D systems generally have momentum-direct low-energy excitons, thus favoring condensation. Our predictions are obtained for ZnPc−MoS 2 using state-of-the-art first-principles calculations with the GW-BSE approach. The exciton energies we predict are in excellent agreement with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Figure b). This large exciton size is comparable to the recently reported CT exciton size (∼10–20 Å) realized in the organic-2D material heterostructures, therefore making the excitons ideal for exciton condensation. We find that the dimer molecule exhibits the same dimerization energies at different twisted angles (θ = 30° and 60°) and therefore equal stability (cf.…”
Section: Does Staggered Type II Band Alignment Ensure the Formation O...supporting
confidence: 73%
“…Figure b). This large exciton size is comparable to the recently reported CT exciton size (∼10–20 Å) realized in the organic-2D material heterostructures, therefore making the excitons ideal for exciton condensation. We find that the dimer molecule exhibits the same dimerization energies at different twisted angles (θ = 30° and 60°) and therefore equal stability (cf.…”
Section: Does Staggered Type II Band Alignment Ensure the Formation O...supporting
confidence: 73%
“…The critical Mott density n c can be determined by the exciton Bohr radius R via nc1normalπR2 ( 15 , 17 , 29 , 30 ). Here, we estimate the exciton Bohr radius R by the root mean square (RMS) radius of the exciton wave function defined as ( 17 )R2=normal〈RMSnormal〉=rr02normalρfalse(rfalse)italicdrnormalρfalse(rfalse)italicdr…”
Section: Resultsmentioning
confidence: 99%
“…revealed that singlet energy transfer from tetracene to WSe 2 occurred in 3 ps, followed by hole transfer contrariwise in 16.5 ps (Figure 6c) [48] . The rapid charge or energy transfer observed in aforementioned heterostructures is a result of a strong intermolecular electronic coupling or hybridization between organic and TMD semiconductors [49] …”
Section: Introductionmentioning
confidence: 93%
“…[48] The rapid charge or energy transfer observed in aforementioned heterostructures is a result of a strong intermolecular electronic coupling or hybridization between organic and TMD semiconductors. [49] Researchers have recently exploited TMDs as viable inorganic counterparts for populating the triplet exciton states of organic semiconductors. For example, Kafle et al studied MoS 2 as a triplet sensitizer for zinc phthalocyanine (ZnPc).…”
Section: D Organic-tmd Heterostructuresmentioning
confidence: 99%